RGD-modified dihydrolipoamide dehydrogenase conjugated to titanium dioxide nanoparticles – switchable integrin-targeted photodynamic treatment of melanoma cells. Issue 17 (1st March 2018) - Dayan, Avraham; Fleminger, Gideon; Ashur-Fabian, Osnat
Abstract : This work presents a UVA switchable integrin-targeted photodynamic therapy in melanoma, composed of an RGD-modified DLDH conjugated to TiO2 nanoparticles, with high selectivity towards integrin-expressing cancer cells. Abstract : The photocytotoxic effect of UVA-excited titanium dioxide (TiO2 ), which is caused by the generation of reactive oxygen species (ROS), is often used in medical applications, such as cancer treatment. Photodynamic-therapy (PDT) is applied in several cancer models including cutaneous melanoma (CM), however the lack of selectivity causing damage to surrounding healthy tissues limits its applicability and novel targeted-delivery approaches are required. As cancer cells often overexpress integrin receptors ( e.g. αvβ3 ) on their cell surface, targeted delivery of TiO2 nanoparticles (NPs) via an Arg-Gly-Asp (RGD) motif would make PDT more selective. We have recently reported that the mitochondrial enzyme dihydrolipoamide dehydrogenase (DLDH) strongly and specifically conjugates TiO2 via coordinative bonds. In this work we have modified DLDH with RGD moieties (DLDH RGD ), creating a molecular bridge between the integrin-expressing cancer cells and the photo-excitable TiO2 nanoparticles. Physicochemical assays have indicated that the hybrid-conjugated nanobiocomplex, TiO2 –DLDH RGD, is producing controlled-release ROS under UVA illumination, with anatase NPs being the most photoreactive TiO2 form. This drug delivery system exhibited a cytotoxic effect in αvβ3 integrin-expressing mice melanoma cells (B16F10), but not in normal cells lacking this integrin (HEK293). No cytotoxic effect was observed in the absence of UV illumination. Our results demonstrate the feasibility of combining the high efficiency of TiO2 -based PDT, with an integrin-mediated tumor-targeted drug delivery for nanomedicine.